Building maintenance policy issues in high rise commercial buildings - Yahya, Mohamad Ridzuan; Ibrahim, Md. Najib (2011)
At present, high rise commercial building is quite complex in implementing a building maintenance policy. The quality, safety and service are the criteria of the building maintenance policy which should be provided and implemented in the high rise commercial buildings in order to sustain their value and economics. It also can benefit to the investment aspect as well as the maintenance activities. The purpose of this paper is to look at the implementation of the building maintenance policy in building maintenance management of high rise commercial buildings in Malaysia. Seven high rise office buildings were investigated through randomly selection in Klang Valley, Malaysia. This study attempts to provide a perspective of in-house building maintenance personnel and outsourced consultant as well as contractors on the maintenance policy practiced in building maintenance management of high rise office buildings through unstructured interviews. This paper presents the preliminary finding of a study on the building maintenance policy issues in the particular buildings. The current maintenance policy procedures in Malaysia are however based on house rule and contract agreement. The weaknesses in the current procedures are the primary problems because they do not explicitly link maintenance needs with performance management, strategic management and facilities management. The results had shown that the scope of building maintenance implemented varies from one building to another. This implies the quality of maintenance is not consistent especially in building performance aspect. The most important finding is that the building maintenance policy standard is not available in all buildings. This research establishes the need to develop a standard of building maintenance policy in high rise commercial building to be enforced legally in order to ensure the consistency of quality, safety and service to end users as well as publics all the time. As a conclusion, building maintenance policy can be a tool in order to measure and value the quality of the maintenance and operation processes improvement link with performance management, strategic management and facilities management